The generalized internal/external frame of reference model with academic self-concepts, interests, and anxieties in students from different language backgrounds - van der Westhuizen, Lindie; Arens, A. Katrin; Greiff, Samuel; Fischbach, Antoine; Niepel, Christoph (Contemporary educational psychology, 2022)
•Academic self-beliefs and motivations form via social and dimensional comparisons.•Higher achievement in one subject can lead to lower self-beliefs in another subject.•Across two verbal subjects, this pattern held for self-concept, interest and anxiety.•The results were equivalent across students from different language backgrounds.•Dimensional comparisons occur in the formation of language motivation and affect. Student motivation and affect play an important role in successful language learning. To investigate the formation of language learning motivation and affect, this study extended the generalized internal/external frame of reference (GI/E) model framework to multiple languages (German and French, along with math) and multiple motivational-affective outcomes (academic self-concept, interest, and anxiety). We examined whether social and dimensional comparisons play similar roles in the formation of students’ self-concepts, interests, and anxieties concerning different languages and whether dimensional comparisons result in contrast or assimilation effects. Moreover, we tested the generalizability of the GI/E model assumptions across students with different language backgrounds. Using a data set comprising virtually all ninth-grade students (N = 6275; 48.0% female) from Luxembourg’s multilingual educational system, our findings indicated (1) clear contrast effects in the formation of self-concept and interest in math, German, and French, and (2) a combination of contrast, assimilation, and no effects in the formation of anxiety in math, German, and French. Using a subsample of 5837 students with valid language information (48.0% female), invariance tests demonstrated that the GI/E achievement–outcome relations operated equivalently across students from different home language backgrounds.